Uma plataforma para acoplamento de modelos de simulação utilizando websockets - Sartori, Jeancarlo (2017)
Simulation models have been used as a way to understand the functioning of a complex system, to envisage gains, to reduce costs and / or as a way to predict future events. In the computational simulation of a complex model, such as those involving environmental and biological phenomena, there will always be a considerable amount of agents that, at some point, will interfere in the natural development of the experiment. It is common, therefore, for scientists to investigate the numerous variations in a multifaceted way, and as scientific knowledge advances, new models are developed and existing ones are updated. Resulting in expensive models to develop and difficult to maintain and improve. So why not use this legacy knowledge by coupling already existing models into a concomitant execution? The main objective of this study is the construction of a computational platform for coupling, where it is possible to configure executions of different models in a single simulation, independent of the programming languages involved in the construction of these models. The researcher s own or known models may also be coupled remotely. The result of this study was a tool that allows the integration of different simulation models in a very simple and transparent way, through the Web. In addition to the legacy knowledge provided by the models, we sought to use the data base of experiments as data source for the configuration of the executions. The coupling takes place through a WebSockets server. Coupling routines, added to model code, manage communication with the server